Pengaruh Online Marketing Dan Harga Terhadap Keputusan Menginap Ditengah Pandemi Covid-19 (Studi Kasus Pada Riche Heritage Hotel Kota Malang) - Muhamad Rizal Fatoni; Nur Hidayati; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThe purposive of this study was to determine and analyze the decision to stay in the Covid-19 pandemic at the Riche Heritage Hotel in Malang City. The variable that can be affected are online marketing and price. This type of research is explanatory research, which means that it explains the causal relationship between the independent variable and dependent variable. The method used is descriptive analyze, which uses quantitative methods to manage dats obtained using questionnaire technology. According to data from Riche Heritage Hotel, 1500 consumers were acquired at that time. In addition, purposeful sampling is performed and the slovin formula is used, a technique used to determine the number of samples up to 93 samples. Based on the above data management, the results show that online marketing and price at the same time have a significant positive impact on the decision to stay in the Covid-19 pandemic, Online marketing has a partial positive influence on the decision to stay in the Covid-19 pandemic, and some prices have an important positive influence on the decision to stay in the Covid-19 pandemic.Keywords: Overnight Decision-Making, Online Marketing and Price